2009
DOI: 10.1055/s-0028-1112136
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Postprandial Glucose Control is Associated with Improved Cardiac/Vascular Function – Comparison of Three Insulin Regimens in Well-controlled Type 2 Diabetes

Abstract: In people with type 2 diabetes (T2DM), hyperglycemia has a negative impact on cardiac function and cardiovascular risk. Beneficial effects of improved postprandial glycemic control have been shown for cardiovascular risk only. To demonstrate these beneficial effects on myocardial function, we investigated well-controlled T2DM patients on three insulin regimens with different impact on postprandial glucose control. For 24 months, 61 T2DM participants in a randomized study had either conventional therapy (CT) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 36 publications
1
33
2
1
Order By: Relevance
“…On the other hand, controversial results have been reported about the effect of glycemic control on the arterial stiffness [6, 21]. In the overall subject population in this study, the HbA1c value decreased from 6.9 to 6.7%, however, this small reduction of the HbA1c value was not associated with any significant reduction of the arterial stiffness.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…On the other hand, controversial results have been reported about the effect of glycemic control on the arterial stiffness [6, 21]. In the overall subject population in this study, the HbA1c value decreased from 6.9 to 6.7%, however, this small reduction of the HbA1c value was not associated with any significant reduction of the arterial stiffness.…”
Section: Discussioncontrasting
confidence: 68%
“…Some studies have reported that the treatment of diabetes is associated with a reduction of the arterial stiffness [69]. Recently, new orally administered dipeptidyl peptidase 4 (DPP-4) inhibitors have become available for the treatment of diabetes [10].…”
Section: Introductionmentioning
confidence: 99%
“…350 Therefore, HbA 1c is only one indicator of risk for microvascular complications of diabetes, and whether HbA 1c is a valid surrogate endpoint for macrovascular disease risk remains uncertain. Investigation into new risk markers that account for factors not captured by HbA 1c that may impact risk of complications 59,351,352 and risk prediction models including these new putative factors is needed. 353 …”
Section: Atherosclerotic Cardiovascular Risk Reduction In Diabetesmentioning
confidence: 99%
“…23 Patients with well-controlled T2DM received either conventional therapy (premixed RHI twice daily; n = 20), intensifi ed therapy (prandial fast-acting insulin analog and NPH insulin at bedtime; n = 24), or supplementary therapy (additional RHI at meals; n = 17). All 3 regimens achieved overall good glycemic control, but PPG excursions were signifi cantly lower in patients receiving intensifi ed or supplementary therapy.…”
Section: Consequences Of Elevated Ppgmentioning
confidence: 99%